Implementasi Perda Nomor 2 Tahun 2022 Terhadap Pengamen Badut Di Rokan Hulu - AMELYA, SISKA; KARMILIA, RISE; NORA NST, ELFI; AULIA, SINDI; HENDRI; NOFRIZAL (Riau Law Journal, 2025)
This study aims to analyze the implementation of Rokan Hulu Regency Regional Regulation Number 2 of 2022 concerning Public Order, especially regarding the presence of clown buskers at traffic light intersections. The phenomenon of clown buskers that is rampant in urban areas of Rokan Hulu is considered to disturb public order and endanger the safety of road users, so it has become a concern for the local government. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through in-depth interviews with Satpol PP officers, clown buskers, and the local community, as well as documentation of related policies. The results of the study show that the implementation of the Regional Regulation has not been optimal. The obstacles faced include limited human resources in the regional regulation enforcement officers, less than optimal socialization to the community, and economic factors that encourage clown busking activities to continue. In addition, there are no alternative solutions from the government for buskers to switch professions properly. In conclusion, although normatively Regional Regulation Number 2 of 2022 has regulated the prohibition of activities that disturb public order, its implementation still requires strengthening in the aspects of supervision, enforcement, and social empowerment. The recommendation from this study is the need for synergy between local governments, law enforcement officers, and social institutions in controlling clown buskers while providing sustainable economic solutions.